Linguistic Semiotic Features in Interior Furnishing Design - Xie, Yixuan; bin Hussin, Ridzuan (Technium Social Sciences Journal, 2021)
Linguistic semiotics has had a huge impact on the development of humanities, especially in architecture and design. There is a close relationship between architecture and language, design and language. As a new subdivision of interior design, interior furnishing design belongs to architectural space, and this connection is inherent. But little research has been undertaken by interior furnishing designers on these issues. This research discusses the relationship between interior furnishing design and language through the research method of case study. The conclusion of this research is that the interior furnishing design and language have a one-to-one similarity in four aspects: formal elements (vocabulary), structural elements (grammar), meaning elements (semantics), and environment elements (context). Therefore, the linguistic semiotic perspective of interior furnishing design will become a powerful tool for people to understand interior furnishing design, as well as an important means for designers to express their creative thinking.